2021
DOI: 10.1186/s12872-021-02134-y
|View full text |Cite
|
Sign up to set email alerts
|

The vicious cycle: a history of obesity and COVID-19

Abstract: Recently, we face a surge in the fast-forward Coronavirus Disease 2019 (COVID-19) pandemic with nearly 170 million confirmed cases and almost 3.5 million confirmed deaths at the end of May 2021. Obesity, also known as the pandemic of the 21st century, has been evolving as an adverse prognostic marker. Obesity is associated with a higher risk of being SARS-CoV-2-positive (46%), as well as hospitalization (113%) and death (48%) due to COVID-19. It is especially true for subjects with morbid obesity. Also, observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…24,25 The epidemiology of COVID-19 incidence based on analyses of large populations shows a clear association with body weight, especially with obesity. 26,27 In a study conducted in a group of medical staff employed at both COVID and non-COVID hospitals, BMI values were higher for those who had an infection compared to those who were not infected. Consistent with our studies, Popkin et al found an increased number of COVID-19-positive individuals among obese ones; in addition, individuals with obesity were more likely to be hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The epidemiology of COVID-19 incidence based on analyses of large populations shows a clear association with body weight, especially with obesity. 26,27 In a study conducted in a group of medical staff employed at both COVID and non-COVID hospitals, BMI values were higher for those who had an infection compared to those who were not infected. Consistent with our studies, Popkin et al found an increased number of COVID-19-positive individuals among obese ones; in addition, individuals with obesity were more likely to be hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bil and Możeńska (2021), the relationship between obesity and Covid-19 represents the perfect vicious cycle [4] . A large 2022 meta-analysis of 208 studies involving more than 3,550,000 participants demonstrated that obese subjects are susceptible to threatening Covid-associated complications; obesity is associated with a 72% (95% CI 1.62–1.84) higher risk of hospitalization and 25% (95% CI 1.19–1.32) higher risk of mortality due to Covid-19; severe obesity is associated with a 2.53 (95% CI 1.67–3.84)-fold higher risk of hospitalization and 2.06 (95% CI 1.76–3.00)-fold higher risk of mortality due to Covid-19 [5] .…”
mentioning
confidence: 99%